2017
DOI: 10.1007/s10554-017-1270-4
|View full text |Cite
|
Sign up to set email alerts
|

Relation of presystolic wave on doppler examination to syntax score in patients with acute myocardial infarction

Abstract: We found that the presence of PSW was related with higher LVEF, lower SXscore and lower stage diastolic dysfunction in patients with AMI. PSW may be used in prediction of the coronary artery disease complexity and it could help risk stratification in patients with AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
1
12
0
1
Order By: Relevance
“…Significant difference was observed in the SYNTAX score between patients with and without PSW ( P = .03), similar to the results in a previous study, performed on the patients with acute myocardial infarction which revealed median SYNTAX scores was significantly lower in the PSW positive group compared to those without PSW [ P = .013] 13 …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Significant difference was observed in the SYNTAX score between patients with and without PSW ( P = .03), similar to the results in a previous study, performed on the patients with acute myocardial infarction which revealed median SYNTAX scores was significantly lower in the PSW positive group compared to those without PSW [ P = .013] 13 …”
Section: Discussionsupporting
confidence: 88%
“…It could be proposed that PSW might be more prevalent in patients with better cardiac function and physiology. It was previously shown that PSW was less frequent in patients with subclinical left ventricular dysfunction 13 …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Presystolic wave (PSW) is an image which is frequently, albeit not necessarily, observed on the outflow tract of the left ventricle (LVOT) later in the diastolic period upon Doppler echocardiographic imaging (13,14). Although PSW's exact prevalence and clinical importance in diverse medical conditions are not well recognized, preliminary evidence suggested that its absence could indicate adverse CV events in patients with overt left ventricular (LV) failure (14,15), subclinical LV dysfunction in asymptomatic HT patients (16), higher Syntax score in patients with acute myocardial infarction (15), worsening arterial elasticity in asymptomatic subjects (13), and increased carotid plaque burden in patients with multiple CV comorbidities (17). Not only its absence, but its velocity was also proposed to have clinical implications (13,14,16,17).…”
Section: Introductionmentioning
confidence: 99%